A Review of Therapeutic Properties and Uses of Salvia officinalis: Review article (Journal of Pharma Insights and Research, 2024)
Sage (Salvia officinalis) is an aromatic perennial herb belonging to the Lamiaceae family, renowned for its culinary and medicinal applications. Its essential oil and various phytochemical constituents, such as α-thujone, β-thujone, camphor, 1,8-cineole, and phenolic compounds like rosmarinic acid, carnosic acid, and carnosol, contribute to its diverse biological activities. The plant exhibits potent antioxidant, antimicrobial, anti-inflammatory, neuroprotective, and anti-diabetic properties. Numerous studies have explored its potential in combating various diseases, including cancer, Alzheimer's, cardiovascular disorders, and diabetes. The essential oil and extracts have demonstrated cytotoxic effects against various cancer cell lines, suggesting their potential as anticancer agents. Additionally, sage has shown promising results in improving cognitive function and memory, potentially benefiting individuals with neurodegenerative diseases like Alzheimer's. Its anti-diabetic effects, mediated through the inhibition of α-glucosidase and enhancement of insulin secretion, make it a valuable candidate for diabetes management. However, it is crucial to consider the potential toxicity associated with the thujone content in sage, as excessive intake may lead to adverse effects. Regulatory bodies have established safe limits for thujone consumption, ensuring responsible use of sage-based products. In conclusion, Salvia officinalis presents a promising avenue for further research and potential therapeutic applications, warranting rigorous scientific investigation to harness its full potential while ensuring safety.